Ferdinand De Saussure's Semiotic Analysis of The Poetry 'My Heart Is a Sheet of Leaves' By Sapardi Djoko Damono - Citra Puspita (Institute of Multidisciplinary Research and Community Service, 2022)
Abstract: This study aims to analyze the poem entitled